Engineering Invention and Innovation Expo 2012 - Lee, Cheng Pay, Ir.; Vivekasugha, Alif Gunalan, Engr. (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org